2013
DOI: 10.1097/hjh.0b013e32835c175f
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure hyperreactivity

Abstract: Essential hypertension is associated with chronic exposure to high levels of inorganic arsenic in drinking water. However, early signs of risk for developing hypertension remain unclear in people exposed to chronic low-to-moderate inorganic arsenic. Objective We evaluated cardiovascular stress reactivity and recovery in healthy, normotensive, middle-aged men living in an arsenic-endemic region of Romania. Methods Unexposed (n=16) and exposed (n=19) participants were sampled from communities based on WHO limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis, we assumed both a constant log-linear (log-transformed water As concentration) and a flexible non-linear (restricted cubic splines with knots at the 10th, 50th and 90th percentiles of log-transformed water As concentration) associations. The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…The median value was assigned as the concentration level for each concentration category and if the median value was not provided directly, the mean or the midpoint values were calculated instead [16,25,45,59,63,[66][67][68][69][70][71][72][73][74][75]. For the calculation of the midpoint value for each concentration category, zero was used as the minimum if not available [16,25,66,[68][69][70][71][72][73]. Furthermore, without available maxima values, the width of the highest concentration category was assumed to be equal to the next lowest category [16,25,66,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to inorganic As (iAs) is associated with skin, bladder, lung and other cancers, 13 chronic lung problems 47 and cardiovascular disease and mortality. 8,9 These effects are generally associated with groundwater As concentrations greater than 50 or 100 μ g/l, though emerging research is beginning to identify elevated odds of skin lesions, 10,11 cancer, 12 respiratory infections and symptoms, 13,14 blood pressure effects, 15 and mortality from cardiovascular and other chronic diseases 9,16,17 from drinking water concentrations below 50 μ g/l.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent U.S. study reported higher odds for hypothyroidism among Hispanics with exposure to 8-22 μg/L drinking water iAs in Texas (OR=2.00, 95%CI 1.06-3.76; p=0.032), which the authors attributed in part to residential location (Gong et al, 2015). A study of low to moderate drinking water iAs exposures in nearby Arad County, Romania demonstrated a positive association with male blood pressure reactivity, an early indicator for hypertension and cardiovascular disease (Kunrath et al, 2013). …”
Section: Discussionmentioning
confidence: 99%